Orientações para elaboração de uma cartilha para profissionais da puericultura baseadas em revisão sistemática de sinais precoces de alerta para TEA em bebês de zero a 24 meses - Duré, Camila Abigail Ocariz (2023)
In recent years there has been an increase in the prevalence of autism spectrum disorder (ASD) raising a need to improve early detection and intervention. The first warning signs for ASD are present before the first year, but children receive the diagnosis much later, which harms their development. Considering that childcare professionals are the first professionals to have contact with babies and their families, the present study aimed to present guidelines for the elaboration of a booklet for these professionals, based on a systematic review of warning signs for ASD in babies aged zero to 24 months. Searches for the review were performed using PubMed, PsycINFO and Scopus platforms. Nineteen reviews containing 100 studies were selected. It was possible to identify motor red flags, from two to 24 months of age and verbal red flags, from four to 24 months, however, it was not possible to identify precise descriptions. Considering the inaccuracy of the descriptions of the red flags, behavioral analytical guidelines were developed for the construction of a booklet for childcare professionals that would overcome the flaws found and that could serve as a guide for the professional in their care of babies from zero to zero. 24 months